PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEADILAN PROSEDURAL DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL STUDI PADA DINAS KEBUDAYAAN DAN PARIWISATA ACEH - Muna, Izzatul; Lautania, Maya Febrianty (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of budgetary participation, procedural justice, and management accounting systems on managerial performance of Dinas Kebudayaan and Pariwisata Aceh. This study used the census method which makes the entire population as a sample. This research was conducted at Dinas Kebudayaan and Pariwisata Aceh. The population in this study were managerial based on structural, including middle-level managers and line-level managers with a total of 31 respondents. This research is an associative quantitative research. The primary data obtained through the distribution of questionnaires were used as a source of research data.. The multiple linear regression with SPSS application version 25 was used as a data analysis method. The test tool on hypothesis one is with t test used in evaluating the hypothesis partially while f test is used to search its influence simultaneously. The results showed that 81.8% of the budgetary participation, procedural justice, and management accounting systems were able to explain the variable managerial performance of Dinas Kebudayaan and Pariwisata Aceh. It is also found that, simultaneously and partially, budgetary participation, procedural justice, and management accounting system have a positive effect on the managerial performance of Dinas Kebudayaan and Pariwisata Aceh.